(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article analyzes groundwater, its reserves, quantity, salinity and conditions of use in irrigation on the example of the world and the territory of Uzbekistan. The measures and necessary recommendations for effective use of underground water are presented